GC analysis of different parts of Tecoma stans (L.) Juss. ex Kunth for fatty acid composition - Anand, Mukul; Basavaraju, R. (Current Botany, 2021)
The study evaluated the fatty acid profile of Tecoma stans (L.) Juss. ex Kunth plant parts. PUFAs were predominant in seed and leaf, except flower, which showed a higher amount of SFAs. Leaf exhibited the highest content of linolenic acid. cis-11,14-Eicosadienoic acid was the major fatty acid observed in leaf and seed. Another health beneficial n-6 FA observed in seed was cis-13,16-Docosadienoic acid. The C18:2n6c: C18:3n3c ratio of 4.75:1 confirms plant seed as an ideal source of n-6 FAs.